Structural features impose tight peptide binding specificity in the nonclassical MHC molecule HLA-E. - O'Callaghan, C; Tormo, J; Willcox, B; Braud, V; Jakobsen, B; Stuart, D; Mcmichael, A; Bell, J; Jones, E (1998)
The crystal structure of the nonclassical human class lb MHC molecule HLA-E has been determined in complex with a prototypic ligand, the nonamer peptide (VMAPRTVLL), derived from the highly conserved residues 3-11 of the human MHC class la leader sequence. The mode of peptide binding retains some of the standard features observed in MHC class la complexes, but novel features imply that HLA-E has evolved to mediate specific binding to a tightly defined set of almost identical hydrophobic peptides from the highly conserved class l leader sequences. These molecular adaptations make HLA-E a rigorous checkpoint at the cell surface reporting on the integrity of the antigen processing pathway to CD94/NKG2 receptor-bearing natural killer cells.